Reliability and Validity of General Health Questionnaire-12 in Chinese Dental Healthcare Workers During the COVID-19 Pandemic - Zhong, Xiaogang; Jin, Xin; Yan, Li; Yang, Lu; Long, Huiqing; Wang, Jing; Wang, Haiyang; Liu, Yiyun; Pu, Juncai; Xie, Peng; Ji, Ping (Frontiers in Psychiatry, 2022)
Background: The General Health Questionnaire-12 (GHQ-12) is a widely used instrument to assess mental health status. However, little is known about its applicability in Chinese healthcare workers. This study aimed to evaluate the reliability and validity of the GHQ-12 in Chinese dental healthcare workers. Methods: Dental healthcare workers participated in the first occupational survey in China conducted by the Chongqing Stomatological Association from February 2021 to March 2021 by filling out GHQ-12. The reliability and validity of GHQ-12 were then tested. Results: A total of 3,020 valid electronic questionnaires were acquired. The positive detection rate of self-reported mental health status was 23.80% (719/3,020). The Cronbach’s α coefficient of the GHQ-12 was 0.892, and the Cronbach’s α coefficient was 0.877~0.888 after the deletion of individual items, and the split-half reliability was 0.843. The correlation coefficient between the item-total score ranged from 0.465~0.762 (P<0.05). The exploratory factor analysis found 2 common factors with a factor load of 0.564~0.818. The confirmatory factor analysis showed that the factor load on the specified items was 0.480~0.790. Conclusions: The two-factor model of GHQ-12 featured good reliability and validity, which could be used to assess the mental health status of Chinese dental healthcare workers.